DOI: 10.11606/d.17.2013.tde-26082013-101348
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da intervenção farmacêutica na adesão ao tratamento medicamentoso do paciente idoso diabético seguido em unidade distrital de saúde

Abstract: Ao meu marido Gustavo, Obrigada por todo apoio, carinho e amor! Você é um companheiro incrível! Sem você eu não teria conseguido! Te amo muito! "É só o amor que conhece o que é verdade." Luiz Vaz de Camões AGRADECIMENTOS A Deus por sempre guiar os meus passos e me conduzir por bons rebanhos! Minha intercessora Nossa Senhora das Graças, pela graça de poder realizar mais um sonho! A minha mãe Rosa, pela dedicação, amor e carinho incondicionais, mesmo quando não gozava de plena saúde! Ao meu pai Reinaldo, pelo es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In view of this, it was ensured that non-adherence to antitumour agents is not exclusive to the population studied. Evidence from studies on the adherence to anti-anticancer agents through this same route of administration shows that cancer patients from other countries and regions of Brazil are also negligent with oral therapy, because they stopped taking their medications at some point during treatment [7,15,[20][21][22][23] and the same occurred with the participants in this work.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In view of this, it was ensured that non-adherence to antitumour agents is not exclusive to the population studied. Evidence from studies on the adherence to anti-anticancer agents through this same route of administration shows that cancer patients from other countries and regions of Brazil are also negligent with oral therapy, because they stopped taking their medications at some point during treatment [7,15,[20][21][22][23] and the same occurred with the participants in this work.…”
Section: Discussionmentioning
confidence: 89%
“…As for the quality of the MGT test used by the researchers, they found that it has been a tool for monitoring adherence applied for many years, validated in the United States to assess the adherence of patients undergoing treatment with antihypertensive drugs [20]. Cancer patients have similar characteristics to patients who are hypertensive in terms of pathological chronicity, past clinical history and prolonged progress, asymptomatology, clinical manifestations with recurrences, criticality and progression to disability or death 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classificação dos níveis de adesão se dará pelos escores: alta adesão, média adesão e baixa adesão. 16,[19][20][21] O BMQ é um instrumento dividido em três sessões onde é possível identificar barreiras à adesão quanto ao regime, às crenças e à recordação em relação ao tratamento medicamentoso, baseado na perspectiva do paciente. 14 É um questionário já validado, traduzido e considerado padrão-ouro, além de já ter sido utilizado em conjunto com o TMG em estudo anterior.…”
Section: Metodologiaunclassified
“…* p-valor calculado a partir do teste de qui-quadrado de Pearson. Fonte: Própria autora, 2023.Rev Bras Hipertens 2024;Vol.31(1):[16][17][18][19][20][21][22][23][24] …”
unclassified